CONFERENCE ON HIV/AIDS VULNERABLE GROUPS, HUMAN RIGHTS AND DEVELOPMENT. November 15-16, 2007, Gaberone, Botswana - Bloom, Leonard; Usoro, Abel (PINS-Psychology in Society, 2025)
This conference was the response by an ad hoc group of administrators, university academics, medical personnel and social workers to the recurrent problems of HIV/AIDS. Financed partly by professionally concerned agencies, by government and by the fees of participants, we were struck by the absence of any speakers or participants who were sufferers, family members or friends. Were any representative or groups of sufferers invited? We were told by an organiser that none were.